2021
DOI: 10.1016/j.rmcr.2021.101444
|View full text |Cite
|
Sign up to set email alerts
|

Successful transcatheter arterial embolization of asymptomatic aneurysm associated with left inferior phrenic artery-to-left pulmonary artery fistula: A case report

Abstract: Cases of inferior phrenic artery-to-pulmonary artery fistulas and those complicated by massive hemoptysis have been rarely reported. A 38-year-old man presented to our hospital with a chief complaint of coughing. Computed tomography (CT) revealed a nodule in the left lower lobe, and contrast-enhanced CT showed inflow of contrast medium into the nodule. CT angiography detected an aneurysm associated with a left inferior phrenic artery-to-left pulmonary artery fistula. Transcatheter arterial embolization (TAE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…At the time, surgical resection of the involved lung lobe was done, with ligation of the connecting systemic arteries to prevent hemorrhage [3] . More recent cases described by Wynne et al, Shimmyo et al, Juergens et al, and Kawakado et al all describe various SA-PAF presentations and their repair using endovascular embolization [1] , [2] , [3] , [4] , [5] . Wynne et al describes a right inferior phrenic artery to right pulmonary artery fistula found incidentally while evaluating for cause of ischemic thalamic stroke, with embolization done to reduce the risk of cor pulmonale [2] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the time, surgical resection of the involved lung lobe was done, with ligation of the connecting systemic arteries to prevent hemorrhage [3] . More recent cases described by Wynne et al, Shimmyo et al, Juergens et al, and Kawakado et al all describe various SA-PAF presentations and their repair using endovascular embolization [1] , [2] , [3] , [4] , [5] . Wynne et al describes a right inferior phrenic artery to right pulmonary artery fistula found incidentally while evaluating for cause of ischemic thalamic stroke, with embolization done to reduce the risk of cor pulmonale [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Juergens et all describe a right inferior phrenic artery to right pulmonary artery fistula in a woman with chronic dyspnea; 2 separate embolizations were performed due to the systemic side having connections with the right lateral thoracic, hepatic, and inferior epigastric arteries [5] . Kawakado et al describe finding a left inferior prhenic artery to left pulmonary artery fistula in a man with acute cough, with embolization done to prevent future development of hemoptysis [1] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations